POST-MAGMATIC EVOLUTION OF THE VOLCANIC STRUCTURES IN THE CENTRAL VYHORLAT-HUTYNSKA RIDGE: A STRUCTURAL-MORPHOMETRIC ANALYSIS - Андрієць, Т. (Київський національний університет імені Тараса Шевченка, 2014)
The volcanic ridge is a region with tectonic-magmatic structures characterized by a specific tectonic pattern, geophysical fields and topography. These structures being well-marked features of the relief, their evolution can be traced by employing geomorphological methods. The structural-morphometric method developed by P. Filosofov can be used for both a detailed analysis of recent and ancient relief and reseach into the history of tectonic movements. This research is aimed at determining the postmagmatic history of the volcanic structures and estimating the amplitudes of the recent movements using detailed data on the structural-morphometric surfaces of different genesis and order. The classic structural-morphometric technique has been used for the first time to study the folded area of the Ukrainian Carpathians. GIS have been used to create maps of the stream orders and watersheds, as well as the basic and summit surfaces for the area under study. A program module "Morphometry" has been designed for a more detailed analysis of the relief evolution and tectonic movements. There have been created maps of the residual relief and local erosion of rocks, basic and summit differences of adjacent orders, summit-basic differences of single order. Geological, geophysical data and structural-morphometric indices were analyzed to determine the attitude of the zones combining complex local tectonic units. There have been defined five stages in the tectonic activity of the Chynadiyivsk, Puznyakivsk, Grabivsk tectonic-magmatic structures and Obavskyyi Kamin, Shkitena, Synyak, Dekhmaniv ancient volcanoes. The obtained results are of crucial importance in pushing back the frontiers of contemporary geodynamics, determining the correlations between underground and exogenous processes, and studying natural hazards. Our research results can be used to trace the evolution of relief and the development of tectonic units in other areas of the folded Carpathians. The designed module can be of practical use in modelling morphometric surfaces of different order and genesis, which will enhance the understanding of morphogenesis and the neotectonics of complex mountainous volcanic relief terrain.

Вулканічний хребет є одним з районів, де магматичні структури добре виражені в тектонічній будові, в геофізичних полях та сучасному рельєфі, що дозволяє застосовувати низку геолого-геоморфологічних методів для їх аналізу та еволюції. Структурно-морфометричний аналіз В. Філософова є одним з методів, за допомогою якого виконується ґрунтовний аналіз сучасного і палеорельєфу та відтворюється історія тектонічних рухів території. Метою досліджень є відтворення постмагматичної еволюції вулканічних структур в межах центральної частини Вигорлат-Гутинського вулканічного хребта та визначення амплітуд новітніх рухів на основі детального аналізу структурно-морфометричних поверхонь різного генезису та порядків. В межах гірськоскладчастої області Українських Карпат класична методика структурної морфометрії застосовується вперше. Для території дослідження в середовищі ГІС побудовано карти порядків долин та вододілів, базисні та вершинні поверхні. З метою автоматизації морфометричних побудов створено програмний модуль "Morphometry", за допомогою якого побудовано карти залишкового рельєфу та локального розмиву, різницеві базисні та вершинні суміжних порядків, вершинно-базисні одного порядку та їх різниці. Комплексний аналіз наявних геологогеофізичних даних та структурно-морфометричних показників дав можливість визначити просторове положення зон, в межах яких складно поєднані локальні тектонічні структури, перетинаються розломні порушення різного рангу, генезису і простягання, та простежити їх неотектонічну активність. Визначено п'ять етапів тектонічної активності тектономагматичних структур Чинадіївської, Пузняківської, Грабівської та вулканокупольних структур (палеостратовулканів) Обавського Каменю, Шкітени, Синяк, Дехманів. Одержані результати важливі для більш глибшого пізнання сучасної геодинаміки, встановлення взаємозв'язків між глибинними процесами та зовнішньою динамікою, визначення закономірностей поширення небезпечних геологічних процесів. Результати досліджень є основою для реконструкції еволюції рельєфу, розвитку структурно-тектонічних одиниць в різних регіонах Карпатської гірськоскладчастої області, а використання розробленого модуля дає можливість будувати морфометричні поверхні різного порядку та генезису з метою вивчення процесів морфогенезу та неотектоніки територій зі складним гірським вулканічним рельєфом.
ПОСТМАГМАТИЧНА ЕВОЛЮЦІЯ ВУЛКАНІЧНИХ СТРУКТУР ЦЕНТРАЛЬНОЇ ЧАСТИНИ ВИГОРЛАТ-ГУТИНСЬКОГО ПАСМА ЗА ДАНИМИ СТРУКТУРНО-МОРФОМЕТРИЧНОГО АНАЛІЗУ
Keywords: structural morphometry; tectonic movements; GIS; relief; morphogenesis; структурна морфометрія; новітні рухи; ГІС; рельєф; морфогенез